Cathode Spots of Vacuum Arc Discharges. (April 2015) - Bystrov, Yu. A.; Kostrin, D. K.; Lisenkov, A. A; Vetrov, N. Z.
Abstract Vacuum arc discharge is used for formation of pure metal and complex combined coatings, and also for the impact of the discharge on a surface to remove superficial contaminants. Physical processes observed in an arc discharge are mostly determined by the behavior of cathode spots, which are fundamentally unstable plasma formations and are characterized by a certain value of average lifetime. Reliable stabilization of the cathode spots and controlling their movements on the working surface grants the technology a grater importance in application.